KONSEP PERILAKU DALAM PSIKOLOGI ISLAM TELAAH KOMPREHENSIF TERHADAP KONSTRUK AKHLAK, NAFS, DAN INTERVENSI PERUBAHANNYA - Dzihni Mutawakkil Alalloh; Titin Nurhidayati (PT. Sulthan Journal Publisher, 2025)
Islamic psychology provides a distinctive framework for understanding human behavior, which is fundamentally rooted in the inner condition of the self (nafs) and manifests as moral character (akhlak). The growing demand for spiritually integrated behavioral models motivates this study to conduct a systematic and comprehensive review of behavioral concepts within Islamic psychological literature, aiming to identify its core constructs and map the typology of behavior emphasized in this tradition. This study employs a Systematic Literature Review (SLR) or conceptual review method, analyzing and synthesizing classical interpretations of primary sources (the Qur’an and Hadith) by seminal scholars such as Al-Ghazali and Ibn Miskawayh, alongside contemporary academic studies. The synthesis reveals that behavior in Islam is classified into Akhlak Mahmudah (praiseworthy behavior) and Akhlak Mazmumah (blameworthy behavior), with their quality determined by the degree of purification of the nafs. Praiseworthy behavior encompasses both a vertical dimension (relationship with God, such as tawakkul) and a horizontal dimension (social relations, such as ‘adl and ṣidq). Furthermore, behavioral formation and transformation in this tradition are centered on the spiritual processes of takhalli, tahalli, and tajalli. It is concluded that Islamic behavior represents a stable manifestation of the soul’s condition, motivated by faith rather than merely shaped by environmental stimuli. These findings carry significant implications for the development of personality assessment instruments and the design of effective, holistic Islamic counseling strategies.